The Effect of Exercises Pursed Lips Breathing (PLB) Changes To Scale Of Breathlessness and Oxygen Saturation In COPD Patients At Hospital Dr. Soedarso Pontianak - Widoroni, Christianus Eko Purwanto; Andri, Florensius; Kristian, Eben Haezar (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a narrowing of the air flow caused by inflammation in the airways resulting in the shortness of breath and reduced oxygen levels in the blood thereby affecting patients’ quality of life.Purpose: The purpose of this study was to determine the effect of exercise on the PLB to Scale of Breathlessness and oxygen saturation (SaO2) in COPD patients.Methods: The research method utilized quasi experimental design with randomized pretest-posttest control group. Sample of 68 respondents (60 respondents PLB group, and 8 respondents control group) was recruited through total sampling technique.Result: Independent t-test showed difference of decreasing Scale of Breathlessness (p=0.018) & increasing of SaO2 (p=0.023) between PLB & control group. The results of Multiple linear regression test showed an effect of PLB on a Scale of Breathlessness (p=0.030) and SaO2 (p=0.002).Conclusion: It can be concluded that the PLB exercises influenced changes in the value Scale of Breathlessness and SaO2.